Over 40 years with jumping spiders: on the 70th birthday of Wanda Wesołowska - Wiśniewski, Konrad (Zootaxa, 2020)
Professor Wanda Wesołowska (maiden name Nowysz)—an internationally recognised expert in the taxonomy of jumping spiders (Araneae: Salticidae)—was born in Włocławek (Central Poland) on 11 August 1950. Wanda spent her youth and received her primary and secondary education in Szczecin (NW Poland). After finishing school in 1968, she entered the Adam Mickiewicz University in Poznań, where she studied biology. Wanda graduated with a MSc degree in 1973. Her thesis was devoted to birds and was titled “Observations on the water and marsh birds on the storage-reservoir on the Vistula river near Włocławek during migration seasons”. This research was published as a scientific paper (Nowysz-Wesołowska 1976). Thus, Wanda began her scientific career with research on birds, an interest that is not uncommon among arachnologists (e.g., Pontus Palmgren, Michael I. Saaristo and Eugène Simon). This passion was shared with her future husband Tomasz Wesołowski. While still a student, Wanda undertook several regional field trips and published four papers on birds, with most of them being co-authored with Tomasz (Nowysz & Wesołowski 1972, 1973a,b; Nowysz 1973). Recently, Wanda and Tomasz celebrated the 40th anniversary of their marriage with another joint paper devoted to the ecology of the fluke Leucochloridium and its effect on the behaviour of the snail Succinea putris (Wesołowska & Wesołowski 2014). Wanda and Tomasz have one daughter, Olga, who currently works at the Department of Biophysics and Neurobiology at the Wrocław Medical Unversity (Poland), and a grandson, Mikołaj.